Upaya Pengenalan Literasi Keuangan Dini bagi Anak-Anak melalui Program Bimbingan Belajar di Desa Siantar Narumonda - Anjelina Putri Manurung; Luminda Pasaribu; Nelli Ferina Simanullang; Uly Arta Hutabarat; Tetty Manullang (Asosiasi Riset Ilmu Matematika dan Sains Indonesia, 2025)
This community service activity aims to introduce financial literacy from an early age to children in Siantar Narumonda Village through an interactive and educational tutoring program. Financial literacy is an important skill that must be instilled from an early age so that children are able to manage their finances wisely in the future. This activity uses a qualitative descriptive approach to describe the execution process systematically. The program was implemented by students of the Tarutung State Christian Institute as part of the Community Service and Service Lecture (KPPM), targeting 35 children aged 1–12 years. The program was implemented for one month and two weeks, three times a week. The material presented was in five main topics: the importance of financial literacy, tips for managing finances, saving, getting to know money and how to manage it, and getting to know banks and financial institutions. The delivery of the material was carried out through fun methods such as games, simulations, short stories, and group discussions. Evaluation was carried out through participant observation, question and answer sessions, and visual documentation. The results of the activity showed that the children experienced an increase in understanding of the basic concepts of financial literacy and began to apply positive habits in managing finances. This activity is also a means of meaningful learning for implementing students. With an interesting and structured approach, this activity provides significant educational and social impacts. Early financial literacy has proven effective in forming a generation that is financially intelligent and responsible in managing economic resources.